ANALISIS PROSPEK POLITIK BURUH PASCA PEMILU 2014 - Triyono, Triyono (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2016)
The reformation era has changed the condition of political economic, social and cultural. Its mean that the political system can be impact on labours mobility. The labour try to enter the political practice by participating in legislative elections. Actually, they haven’t be able to get into parliament. In the 2014’s general election, there is no labour party as participants. On the other side, the labours has been struggling with its own problems, especially in the problems of fragmentation and organizing. In order to seek the existence of labours in Indonesian politics post 2014’s general election by elaborating librarian data and discussion with experts. This article was described by descriptive analysis which is explained the phenomena of labours in politics. The conclusion was the prospect of labours in 2014’s general election doesn’t win the political contestation, because of several factors influence it both in the internal and external.